Open innovation and its applicability in Vietnam - Binh, Nguyen Dinh; Cuong, Nguyen Manh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Open innovation is a type of non-traditional innovations or it is, in a more exact way of speaking, a new concept to do innovations differently from the ways they have been conducted. The Open innovation is considered as strategy for innovations in the era of knowledge economy and scientific and technological (S&T) revolution. In this new era, there are three factors which attract our attention, namely: i) the technological amplitudes always go beyond capacities of any organization; ii) the changes of technologies go with very high speed; and iii) costs of investments for research and development (R&D) are huge which a single organization has almost no way to afford. In the traditional way to do innovations, the process always passes within a single organization and this type of innovations is usually called “Close innovation”. In the new concept innovations, the process is coordinated between numerous organizations for settlement of a big size problem because of the three above noted reasons. Then the new concept innovations are called the “Open innovation”. This paper deals with basic matters of Open innovations with purpose to introduce the aspects of the Open innovation, to exchange related visions an d to make notes on its applicability in Vietnam. Code: 15081102